Editorial of International Journal of Pharmacy and Integrated Health Sciences - Abubakar Munir (International Journal of Pharmacy & Integrated Health Sciences)
The International Journal of Pharmacy & Integrated Health Sciences (IJPIHS) began in 2021 and its achievement is deceptive in the number of manuscripts submitted and the diversity of scientific themes comprised by the journal. We trust that IJPIHS should endure serving a wideranging concern dealing with the specialized area of Pharmaceutical and Biological Sciences. Submission of a paper to IJPIHS infers that all the corresponding and co-authors should be aware of the manuscript submission and it may not be under consideration and/or not be the part elsewhere. This journal targets to inaugurate a platform for providing research ideas on novel developing tendencies in pharmaceutical and integrated health sciences.